2020
DOI: 10.1212/nxi.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of myelin oligodendrocyte glycoprotein antibody in multiple sclerosis

Abstract: ObjectiveTo address the frequency of myelin oligodendrocyte glycoprotein (MOG) antibody (Ab) in an unselected large cohort of adults with MS.MethodsThis is a cross-sectional study in 2 MS expert centers (Lyon and Strasbourg University Hospitals, France) between December 1, 2017, and June 31, 2018. Patients aged ≥18 years with a definite diagnosis of MS according to 2010 McDonald criteria were tested for MOG-Ab by using a cell-based assay (CBA) in Lyon and subsequently included. Positive samples were tested by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 10 publications
0
51
0
1
Order By: Relevance
“…The serologic detection of MOG-IgG is useful diagnostically and the features of the antibody may provide insight into pathogenesis. A recent large study of MOG antibodies in MS showed it is detected in only 0.2%, highlighting its utility in discriminating from MS [8]. While in our study we used two sites for MOG-IgG detection, our multi-center collaborative studies have shown the live-cell based MOG assay cut-offs show consistent results across centers for a non-MS phenotype [77].…”
Section: Discussionmentioning
confidence: 62%
“…The serologic detection of MOG-IgG is useful diagnostically and the features of the antibody may provide insight into pathogenesis. A recent large study of MOG antibodies in MS showed it is detected in only 0.2%, highlighting its utility in discriminating from MS [8]. While in our study we used two sites for MOG-IgG detection, our multi-center collaborative studies have shown the live-cell based MOG assay cut-offs show consistent results across centers for a non-MS phenotype [77].…”
Section: Discussionmentioning
confidence: 62%
“…138 The second study analysed serum samples from 685 consecutive patients with MS, and found only two of them (0.3%) were MOG-IgG positive. 139 Both studies clearly indicate that MOG-IgG is rare in MS and if present indicate either insufficient assay specificity or an inappropriate clinical diagnosis.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…The proof of serum autoantibodies directed against aquaporin-4 (AQP4-IgG) in around 80% of cases established NMOSD as a distinct disease from multiple sclerosis (MS) (7)(8)(9)(10). In a subgroup of AQP4-IgG negative NMOSD patients serum antibodies targeting the myelin oligodendrocyte glycoprotein (MOG-IgG) were detected (11)(12)(13)(14)(15)(16). MOG-IgG+ patients with clinical and neuroimaging characteristics of NMOSD are currently discussed as a different disease entity (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%